Proyecto de factibilidad para la creación de una empresa de confección y comercialización de pantalones y chaquetas en tela de mezclilla para dama en la ciudad de Loja - Caraguay Zhingre, Alex Michael (2023)
The province of Loja is recognized for its unique handicrafts and textiles where labor predominates, the business idea belongs to this sector that contributes more than 7% to the national manufacturing GDP, according to the INEC 158,000 people work. The main objective of this study is to know the feasibility of making and marketing denim pants and jackets for women in the city of Loja, the type of study is descriptive with a mixed approach, the information was obtained using the survey of a study population of 58,121 women from 15 to 24 years of age, detecting in it an unsatisfied demand of 68,866 pants and 13,866 jackets; the best location for the plant is the Loja industrial park; the production time of the pants is 85 minutes and the jacket is 115 min, an installed capacity of 5,460 pants and 2,912 jackets per year was determined, of which 100% of this capacity will be used in pants and in the same way in jackets, this will participate in the market with 7.79% in pants and 19.83% in jackets; the implementation of the project will generate 15 jobs; the company name will be “What Is Love Cía. Ltd.”. For its implementation, $72,820,58 is required, 58.80% of which will be financed with own capital and 41.20% by a loan. The NPV of $76.241,55 was obtained; the IRR of 38,83%; the benefit-cost ratio of $1.19; the capital recovery period will be 3 years and 17 days; The project is not sensitive to an increase in costs of 3,91% and 3,32%, in a decrease in income, with this it is concluded that the project is feasible.